2000
DOI: 10.1093/nar/28.12.2286
|View full text |Cite
|
Sign up to set email alerts
|

An aryl hydrocarbon receptor conformation acts as the functional core of nuclear dioxin signaling

Abstract: DNA-complexed heterodimers of the aryl hydrocarbon receptor (AhR) with the Ah receptor nuclear translocator (Arnt) are the molecular switches for nuclear signaling of 2,3,7, 8-tetrachlorodibenzo-p-dioxin (TCDD). AhR-Arnt heterodimers regulate genes involved in the metabolism of xenobiotics or fatty acids and various genes important for growth and differentiation. In this report several potent methods, such as the limited protease digestion, gel shift and gel shift clipping assays, allowed the investigation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…It is reasonable to assume that the binding of TCDD to AhR must also elicit some initial conformational change to enable the release of associated proteins (e.g., hsp90, AIP) that are known to comprise the nonligand-occupied AhR complex) and subsequent dimerization with Arnt. Kronenberg et al (2000) reported detection of a ϳ35-kDa fragment of […”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to assume that the binding of TCDD to AhR must also elicit some initial conformational change to enable the release of associated proteins (e.g., hsp90, AIP) that are known to comprise the nonligand-occupied AhR complex) and subsequent dimerization with Arnt. Kronenberg et al (2000) reported detection of a ϳ35-kDa fragment of […”
Section: Discussionmentioning
confidence: 99%
“…The structural diversity of endogenous ligands may induce differential conformations of the ligand-bound receptor that ultimately dictate varying biologic activities (Lees and Whitelaw, 1999;Kronenberg et al, 2000;Patel et al, 2009;Murray et al, 2010a,b;Jin et al, 2012). Synthesis or accumulation of distinct endogenous ligands within certain cell types or tissues could mediate the tissue/cell selective activity of AHR.…”
Section: Possible Mechanism Of Ahr Activation By Low-molecularweight mentioning
confidence: 99%
“…However, the biological significance of ARNT-bHLH tetramerization is unclear since the cellular concentration of ARNT has not been established. Furthermore, the PAS-A domain, which is critical for the heterodimerization of AHR and ARNT and is not present in the bHLH peptide, could play a significant negative or positive role in ARNT homodimerization (44). Comparison of the sensitivity to ionic strength or other solution parameters of ARNT homodimers with ARNT heterodimers (e.g.…”
Section: Effects Of Poly(d[i⅐c]) On Equilibrium Binding-asmentioning
confidence: 99%